Circular economy and olive mill wastewater management—from production to direct land application and short-term effects on soil properties - Kapellakis, Iosif E.; Tzanakakis, Vasileios A.; Kabourakis, Emmanouil M. (Frontiers in Sustainability, 2025)
Olive mill wastewater (OMW) is the most important aqueous by-product generated during olive oil extraction from olive fruit. Due to the large quantities produced in short periods, OMW exhibits high phytotoxicity and a high level of organic pollution, which presents a serious environmental concern. There are two approaches to effectively managing OMW and its impacts. The first one concerns treatment, which involves a combination of physical, chemical, and biological processes adopted within a specific and predetermined framework. The second one concerns land treatment, which dates back to Minoan times and is based completely on natural processes. This, as adopted in the modern era and favored by the enforced legal framework of various olive oil-producing countries, refers to high loading rates of pretreated OMW and aims to assess soil treatment potential and address future environmental impacts. However, despite its environmental benefits, this approach is not entirely consistent with the principles of the circular economy (CE). In contrast, direct application of untreated OMW to the orchards that generate it, immediately after production, is considered promising and ensures the sustainability and adoption of CE principles through reuse. For this reason, a holistic approach to OMW management was adopted, covering all stages of OMW, from production to application, with minimal impact. The purpose of this study was to (a) investigate and evaluate current by-product management techniques in the Messara basin, Crete, an area highly affected by increased OMW quantities, and (b) assess the short-term effect of OMW land application on soil properties. Analysis of the results indicates that current management practices lack efficiency, causing severe environmental impacts; the enforced legal framework concerning land application cannot be fully adopted. In contrast, OMW land application onto olive orchards directly after production does not cause, as expected considering the literature, any adverse effects on soil properties; instead, it increases nutrient availability and maintains soil organic matter (SOM). Along with the soil effects, the present study provided practical information and guidance on OMW application rate and timing to facilitate farmers, policymakers, and decision-makers. Overall, the findings of the study suggest that direct land application should be considered as an alternative solution to effectively manage the negative impacts of by-products. This is fully consistent with the basic CE principles, climate change adaptation, and established Sustainable Development Goals (SDGs).